2008
DOI: 10.1097/aud.0b013e318168d94d
|View full text |Cite
|
Sign up to set email alerts
|

Production and Perception of Speech Intonation in Pediatric Cochlear Implant Recipients and Individuals with Normal Hearing

Abstract: As a group, pediatric CI recipients do not show mastery of speech intonation in their production or perception to the same extent as their NH peers. Pediatric CI recipients' performance levels in the production and perception of speech intonation contrasts are moderately correlated. Intersubject variability exists in pediatric CI recipients' mastery levels in the production and perception of speech intonation contrasts. These findings suggest the importance of addressing both aspects (production and perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
138
3
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(154 citation statements)
references
References 59 publications
8
138
3
5
Order By: Relevance
“…This limited number of electrode contacts takes over the task of the IHC and the frequency discrimination is accordingly poor compared to the natural hearing sensation. [6][7][8] For example, hearing perception of CI-treated patients is hindered in the event of multiple speakers or in order to perceive complex sounds such as music. 9 To improve frequency discrimination, the number of electrode contacts should be increased.…”
Section: Introductionmentioning
confidence: 99%
“…This limited number of electrode contacts takes over the task of the IHC and the frequency discrimination is accordingly poor compared to the natural hearing sensation. [6][7][8] For example, hearing perception of CI-treated patients is hindered in the event of multiple speakers or in order to perceive complex sounds such as music. 9 To improve frequency discrimination, the number of electrode contacts should be increased.…”
Section: Introductionmentioning
confidence: 99%
“…This finding both supports and extends upon previous literature that has shown that imitation is problematic for children with hearing loss (Chin et al, 2012;Cleary et al, 2002;Dillon et al, 2004;Ertmer & Goffman, 2011;Ertmer et al, 1997;Nakata et al, 2012;Peng et al, 2008;Sehgal et al, 1998). For example, children with hearing loss have been shown to have difficulty producing exact imitations of non-words, and their attempted repetitions tended to have fewer syllables as compared to the target (Cleary et al, 2002;Dillon et al, 2004).…”
Section: Infant and Mother Vocalizationssupporting
confidence: 87%
“…Previous studies suggest that imitation abilities are negatively affected in infants with HI (Chin, Bergeson, & Phan, 2012;Dillon, Cleary, Pisoni, & Carter, 2004;Ertmer & Goffman, 2011;Ertmer, Kirk, Sehgal, Riley, & Osberger, 1997;Nakata, Trehub, & Kanda, 2012;Peng, Tomblin, & Turner, 2008;Sehgal, Kirk, Svirsky, Ertmer, & Osberger, 1998). While there is very little past research that investigates naturalistic vocal imitation in hearing impaired infants, there are several studies that looked at imitative abilities of older children with cochlear implants (CIs) by using both non-word and whole word repetition tasks in laboratory settings.…”
Section: Contingent Communication Including Vocal Matching Is Negatmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the perception of prosody is generally poorer in CI users compared to normalhearing listeners (e.g., Holt and McDermott, 2013;Holt et al, 2016;Marx et al, 2015;Meister et al, 2009Meister et al, , 2011Morris et al, 2013;Peng et al, 2008Peng et al, , 2009. Although the temporal envelope of speech carries information related to duration, pauses, and amplitude, the reduced spectral and temporal resolution in CI listening (e.g., Oxenham and Kreft, 2014) negatively impact the perception of prosody.…”
Section: Introductionmentioning
confidence: 99%